2012
DOI: 10.3390/s121217463
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept for Quantifying the Complicated Kinematics of the Cervical Spine and Its Application in Evaluating the Impairment of Clients with Mechanical Neck Disorders

Abstract: Mechanical neck disorder (MND) is one of the most common health issues and is characterized by restricted cervical mobility. However, traditional kinematic information often focuses on primary movement in the cardinal plane, which seems insufficient to fully determine the kinematics of the cervical spine because of the complexity of the anatomical structures involved. Therefore, the current investigation aimed to modify the concept of the three-dimensional workspace to propose an objective mathematical model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Distinct modulations of motor unit synchronization among patients with MND and asymptomatic individuals observed in the present investigation subscribe to the assertion that patients with MND used altered neuromuscular control strategies to achieve the prescribed task compared to asymptomatic subjects. Since the plastic modulation of motor unit synchronization is generally thought to originate from common synaptic input branched presynaptic neurons [31, 32], it is most likely that the reduction in motor unit synchronization reflects the poor cortico-motoneuronal connections, which would be consistent with decreases in muscular strength and presences of jerky or irregular movements for patients with neck pain [2, 9, 10]. Furthermore, another interesting issue should be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct modulations of motor unit synchronization among patients with MND and asymptomatic individuals observed in the present investigation subscribe to the assertion that patients with MND used altered neuromuscular control strategies to achieve the prescribed task compared to asymptomatic subjects. Since the plastic modulation of motor unit synchronization is generally thought to originate from common synaptic input branched presynaptic neurons [31, 32], it is most likely that the reduction in motor unit synchronization reflects the poor cortico-motoneuronal connections, which would be consistent with decreases in muscular strength and presences of jerky or irregular movements for patients with neck pain [2, 9, 10]. Furthermore, another interesting issue should be further elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, they also found greater spectral entropy in the clinical group. 20,21 Other lab studies have identified that the displacement, 22,23 velocity, 23,24 acceleration, 19,22 and smoothness (jerk index) 17,23 of neck motions in people with neck pain are significantly different from matched controls. However, the usefulness of these approaches has been criticized, as the parameters are sensitive to the envelope of motion and velocity 18,25 and are not accessible for routine clinical practice.…”
Section: Introductionmentioning
confidence: 98%
“…Multifactorial origins, such as prolonged workloads, poor work postures and even psychological distress, are likely to be associated with this musculoskeletal condition [9][10][11]. Except for cervical kinematic and kinetic aberrations [12][13][14][15][16][17][18][19][20][21], previous electrophysiological findings have demonstrated the appearance of neuromuscular adaptations for patients with neck pain [22][23][24][25][26][27][28][29][30]. Increased activation of the superficial cervical flexor muscles and the upper trapezius [23][24][25][26][27]30] and reduced activation of the deep cervical flexor muscles [27][28][29] account for the compensatory modulation of hyper-activation of the superficial cervical flexor muscles for the weak or inhibited activation of the deep cervical flexor muscles in neck pain patients [25,26].…”
Section: Introductionmentioning
confidence: 99%